Entrepreneurial academics and academic entrepreneurs: a systematic literature review. (2018) - Miller, Kristel; Alexander, Allen; Cunningham, James A.; Albats, Ekaterina
Universities are now viewed as key economic actors within regions and are central actors in shaping and influencing entrepreneurial ecosystems. This has meant that universities now have to become more entrepreneurial in offerings, outlook and culture. However, a core actor in this process who is often overlooked is the academic. The ability of an academic to effectively transfer knowledge to industry is key to universities achieving their entrepreneurial mission and ambition. This paper explores the changing roles of academics to identify key distinctions between entrepreneurial academics and academic entrepreneurs. This is done through a systematic literature review spanning 25 years drawing on selected high impact journals in innovation, entrepreneurship and higher education studies. We categorise the types of activity that academics typically engage in and identify the motivations and challenges they face. From this, we identify two types of academics, the entrepreneurial academic and academic entrepreneur. We posit that there is a need for both types of academics to contribute to the success of the entrepreneurial university and conclude by outlining some avenues for future research.